측방 두부규격방사선사진을 이용한 이공의 위치 - 이승훈; 김동열; 정소윤 (Han'guk Ch'iwisaeng Hakhoe chi, 2010)
Objectives : This study is aimed to prevent the damage to the inferior alveolar nerve during the orthognathic surgery. Methods : The control group consist of 50 patients with class I occlusion. The experimental group consist of 50 patients with class III malocclusion. The cepalometric radiography was used to evaluate the position of the mental foramina. Results : In the first, mental foramen position of class III was more inferior 0.85 mm in the distance between base of mandible and mental foramen. But the distance between occlusal plan and mental foramen had not statistically significant. Secondly, mental foramen location of Mandibular Prognathism was more anterior 0.91 mm in the distance between coronal plane of mandible included pogonion point and mental foramen. Also, the distance of occlusal-coronal plane of mandible included central incisor and mental foramen had statistically significant. The mental foramen location of class III was more anterior 4.81 mm than class I patients. Conclusions : The result of this study could help the clinicians to apprehend fundamental data with various facial skeletal types for any related researches about the location of the mental foramina for other purposes. KCI Citation Count: 0